Performance and Maintenance Improvement of UG Electrical Equipment PT. Freeport Indonesia - Bosco, Don; Simatupang, Togar M (The Indonesian Journal of Business Administration, 2015)
Abstract. Operation movement from Grasberg to Underground requiring UG Electrical, as the sole electrical maintenances and services provider in underground area, to develop the best maintenance plan to improve effectiveness and efficiencies in performing both maintenances and services activity as there would be expansion in working area and additional equipment to be maintained. Business process reengineering approach is taken as guide in developing methodology to rectify and improve current problem in maintenances and services activity. Current situation analysis is done to describing and analyzing the current (as-is) process map, current symptoms and root cause problem, and resources and capability assessment. Desired target is described by analyzing customer needs and determining performance indicator to achieve it.The results of current versus desired target in performance will be used to analyze performance gap for each performance indicator and inhibitors that causing gap in performance. Development of adequate KPI is proposed in order to rectify gap in performance. New internal business process of maintenances and services also will be developed as activity guidance for all functional teams to achieve desired KPI. . Options in data acquisition, namely SAP, SCADA (equipment telemetry), and shift activity report are considered in order to provide adequate information in KPI’s dashboard development. Keywords: Maintenance plan, performance gap, business process, KPI, dashboard.